Association of central blood pressure and cardiovascular diseases in diabetic patients with hypertension. Issue 42 (October 2017) - Yang, Lei; Qin, Bo; Zhang, Xiaojuan; Chen, Yanrong; Hou, Jian
Abstract : Abstract: To evaluate association of central blood pressure (BP) and cardiovascular disease (CVD) in diabetic patients with hypertension. This was a cross-section study and 360 participants were enrolled. Baseline characteristics were collected and indices of central BP including central systolic/diastolic BP (SBP/DBP), augmentation index adjusted for 75 beats per minute of heart rate (AIx@75) were measured. Participants were separated into with and without CVD groups and between-group differences were assessed. Linear regression analysis was used to evaluate potential risk factors for increased AIx@75. Logistic regression analysis was used to evaluate association between central SBP and AIx@75 with CVD. Mean age was 50.6 years and male participants accounted for 57.8%. Thirty-five and 43 participants had coronary heart disease and ischemic stroke. Compared with participants without CVD, those with CVD were more likely to be male and smokers and had higher glycated hemoglobin level. Additionally, participants with CVD had significantly higher central SBP and AIx@75 compared with those without CVD. Ageing, male gender, and presence of coronary heart disease and ischemic stroke were associated with increased AIx@75, whereas renin–angiotensin–axis inhibitor was associated with reduced AIx@75. After adjusted for traditional risk factors including brachial SBP, both central SBP, and AIx@75 remained significantly associated with CVD, with odds ratio and 95% confidence interval of 1.09 (1.08–1.31) and 1.20 (1.15–1.42), respectively. Diabetic patients with hypertension, ageing, male gender, and presence of CVD are independent risk factors of central BP increase; and increased central SBP and AIx@75 are significantly associated with CVD.